Beta-Cell Adaptation to Pregnancy – Role of Calcium Dynamics - Pretorius, Marle; Huang, Carol (Frontiers in Endocrinology, 2022)
During pregnancy, the mother develops insulin resistance to shunt nutrients to the growing fetus. As a result, the maternal islets of Langerhans undergo several changes to increase insulin secretion in order to maintain glucose homeostasis and prevent the development of gestational diabetes. These changes include an increase in β-cell proliferation and β-cell mass, upregulation of insulin synthesis and insulin content, enhanced cell-to-cell communication, and a lowering of the glucose threshold for insulin secretion, all of which resulting in an increase in glucose-stimulated insulin secretion. Emerging data suggests that a change in intracellular calcium dynamics occurs in the β-cell during pregnancy as part of the adaptive process. Influx of calcium into β-cells is crucial in the regulation of glucose-stimulated insulin secretion. Calcium fluxes into and out of the cytosol, endoplasmic reticulum, and mitochondria are also important in controlling β-cell function and survival. Here, we review calcium dynamics in islets in response to pregnancy-induced changes in hormones and signaling molecules, and how these changes may enhance insulin secretion to stave off gestational diabetes.